THE PRACTICE OF GAZA IN THE SPHERE OF SOCIAL PROTECTION OF CHILDREN SUFFERED IN THE RESULT OF THE MILITARY ACTIONS AND ARMED CONFLICTS: EXPERIENCE FOR UKRAINE - Beluga, Julia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to analyse the social protection of children suffered from the war in the Gaza region and to research the possibilities of using this experience as a practical tool for improving the child social protection system in Ukraine. Particular attention is paid to support of children who have suffered physical and psychological trauma, violence or exploitation in the context of the armed conflict in order to create the effective mechanisms for rehabilitation, protection and integration into society. Research methods: formal logical method and method of system analysis, comparative method and other research methods. Results: an author analyses how the experience of Gaza could help to improve the social protection in Ukraine, in particular, through legal initiatives and rehabilitation programmes for the suffered children. Discussion: an author analyses the similarities and differences in the social protection mechanisms for children suffered from the war in Gaza and Ukraine, with a focus on the problems of mental trauma, injuries, violence and the limited access to education and medical care. Comparing the experiences of Gaza and Ukraine, we can say that both countries face similar challenges, but there are some important differences. In both cases, children suffer from the consequences of armed conflict, including the loss of homes, injury, violence, mental trauma, and disruption of access to education. In Gaza, as in Ukraine, the destruction of infrastructure, including schools and medical facilities, has caused great difficulties in providing assistance to children in need of specialized treatment or education. International organizations, such as UNICEF and the Red Cross, are actively working on the ground, providing humanitarian aid, evacuation and psychological support. In Ukraine, since the outbreak of the war, significant efforts have also been made to ensure the safety of children, including through the creation of temporary shelters, humanitarian aid, and the resumption of education. One of the main challenges is the lack of adequate protection for unaccompanied children, which is critical in both Gaza and Ukraine. In both cases, an important issue is the resumption of the educational process, as destroyed schools become a serious obstacle to children’s access to education. In Ukraine, mechanisms have been created to protect children’s rights through legislative initiatives and rehabilitation programs, but the situation requires even greater response, especially for children who have been abused, injured or become victims of armed conflict. Compared to Gaza, Ukraine has a more developed legal system and more active cooperation with international organizations, which helps to address the urgent problems of children affected by the war more quickly. At the same time, both countries need to focus on ensuring the safety of children, their medical and psychosocial rehabilitation, and restoring their access to education as a key element of their recovery from conflict.